Rutin via Increase in the CA3 Diameter of the Hippocampus Exerted Antidepressant-Like Effect in Mouse Model of Maternal Separation Stress: Possible Involvement of NMDA Receptors - Maryam Anjomshoa; Shakiba Nasiri Boroujeni; Sorayya Ghasemi; Zahra Lorigooini; Ahmad Amiri; Shima Balali-dehkordi; Hossein Amini-khoei (Behavioural Neurology)
Background and Aim. Rutin is a flavonol with neuroprotective activity. The aim of the present study is to investigate the role of the glutamatergic system in the antidepressant-like effect of rutin in a mouse model of maternal separation (MS) stress focusing on histological changes in the CA3 area of the hippocampus. Methods. Mouse neonates were exposed to MS paradigm 3 hours daily from postnatal days (PND) 2 to 14. The control and MS mice were divided separately into 16 groups (n=8) (8 groups for each set) including mice that received normal saline, mice that received rutin at doses of 10, 50, and 100 mg/kg, mice that received NMDA at a dose of 150 mg/kg, mice that received ketamine (NMDA antagonist) at a dose of 0.25 mg/kg, mice that received NMDA antagonist plus a subeffective dose of rutin, and mice that received NMDA plus an effective dose of rutin. Forced swimming test (FST) was performed. Afterwards, the hippocampus was evaluated in cases of histopathological changes as well as expression of NR2A and NR2B genes. Results. Rutin significantly reduced immobility time in the FST. The expression of NR2A and NR2B subunits of NMDA receptor in MS mice was significantly higher than that in the control group. Rutin significantly decreased the expression of NR2B and NR2A subunits in the hippocampus. The CA3 diameter and percentage of dark neurons in the hippocampus of MS mice significantly decreased and increased, respectively, which partially reversed following rutin administration. Conclusion. Rutin, partially, through a neuroprotective effect on the hippocampus exerted antidepressant-like effect. We concluded that NMDA receptors, at least in part, mediated the beneficial effect of rutin.